Labour taxation and employment in trade union models: a partial survey - Erkki Koskela (Bank of Finland, 2001)
This paper uses a union bargaining framework, where the wage rate is negotiated between the representatives of employees and employers and firms unilaterally determine employment, to discuss the relationship between labour taxation and employment.In imperfectly competitive labour markets higher labour taxes income and payroll taxes will increase labour costs and have negative effects on employment.Tax progression tends to moderate wages and boost employment.Moreover, if labour tax bases are unequal due to tax exemptions, the structure of labour taxation matters so that the tax wedge may not be a sufficient statistic to describe the channel of influence of labour taxation.Finally, distortionary effects of labour taxes in more corporatist economies should be smaller than in economies with more decentralised wage bargaining. Empirical evidence though not always very strong supports these notions.
URN:NBN:fi:bof-20140807413
Keywords: 330; union bargaining; labour taxation; tax progression